2022
DOI: 10.3389/fpubh.2021.692461
|View full text |Cite
|
Sign up to set email alerts
|

Differences Regarding Knowledge of Sexually Transmitted Infections, Sexual Habits, and Behavior Between University Students of Medical and Nonmedical Professions in Serbia

Abstract: Aim: The aim of this study is to assess the knowledge of sexually transmitted infections (STIs), sexual habits, and behavior among students of medical and nonmedical students in Serbia.Methodology: The cross-sectional study of 1,273 university students of four undergraduate institutions in Serbia, two of medical and two of nonmedical orientation. A standardized questionnaire, prepared in line with the questionnaire of the European health research—the second wave (European Health Interview Survey—EHIS wave 2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Generally, the reasons for not using contraceptive methods can be found in the lack of knowledge, insufficient level of sexual education and lack of accessibility of healthcare services, the incorrect perception of risks and negative social norms in relation to the premarital sexual activity and pregnancy ( 15 , 16 ). As regards women with lower education levels and socioeconomic status residing in rural areas, significant reasons for not using any contraceptives were the following: husband’s refusal of condom use or husband’s fear of his wife’s infidelity, along with women’s fears of possible side effects of contraceptive use or potential health problems associated with different methods of contraception ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the reasons for not using contraceptive methods can be found in the lack of knowledge, insufficient level of sexual education and lack of accessibility of healthcare services, the incorrect perception of risks and negative social norms in relation to the premarital sexual activity and pregnancy ( 15 , 16 ). As regards women with lower education levels and socioeconomic status residing in rural areas, significant reasons for not using any contraceptives were the following: husband’s refusal of condom use or husband’s fear of his wife’s infidelity, along with women’s fears of possible side effects of contraceptive use or potential health problems associated with different methods of contraception ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cervical cancer screening varies on the territory of the European continent, from one country to another, i.e., Western European countries present a larger scope of women who have been subjected to a Pap smear ( 18 ). The results obtained in the survey, based on the assessment of health behavior in Lithuania, revealed a constant rising trend in the percentage of women being screened for cervical cancer from 60% to 74.2% ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this group of the population is more likely to practice risky sexual behaviors, which include, having sex with multiple partners, having unprotected sex, having sexual intercourse with strangers, and having intoxicated sex, because there are various factors such as lack of adequate sexual education, socio-economic status, family structure, parental education, smoking, illegal drugs or alcohol use, low self-esteem, depression, anxiety, impulsiveness, delinquent behaviors and as well as social norms, that affect their knowledge about STIs, their consequences and prevention [ 7 9 ]. Although undergraduate students in the health area have a greater knowledge of sexually transmitted diseases than students of other disciplines, it has been observed that both groups have deficient knowledge in this regard [ 10 , 11 ]. In line with these facts, we recently reported a high incidence of HPV infection in a cohort of female health science university students [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study in Italy, students had insufficient knowledge on the prevention of STIs with some indicating that birth control pills can also prevent infections (Visalli et al 2019 ). It was further revealed that most students lacked sufficient knowledge on the complications of STIs (Subotic et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%